Application of Airport Concessions to The Status of Airport Business Entities Owned by State-Owned Enterprises - Arie Ahsanurrohim; Tri Hayati (Journal Research of Social Science, Economics, and Management, 2023)
Defining concessions will always be related to the concept of Public Private Partnership (PPP) and privatization of the public sector. Broadly speaking, PPP is a long-term engagement between the Government and/or public bodies and business entities, while privatization means the transfer of something under the control of the public sector to the private sector followed by commercialization. These things are in line with the concept of Concession, which is basically the transfer of management of a service/product which is basically the responsibility of the government to the private sector with a return from the government budget or revenue obtained directly from the end user (consumer) of the project and/or service. Based on Article 235 of Law Number 1 of 2009 concerning Aviation, airport services carried out by airport business entities are carried out based on concessions and / or other forms in accordance with the provisions of laws and regulations provided by the Minister and stated in the agreement. Currently in Indonesia one of the largest airport management business entities in Indonesia is PT Angkasa Pura I which was previously entirely owned by the Ministry of State-Owned Enterprises of the Republic of Indonesia, but is now controlled by PT Aviasi Pariwisata Indonesia (Persero) which is a State-Owned Enterprise. This creates a complexity in connection with the imposition of concessions, considering that based on its capital structure, PT Angkasa Pura I contains separated state wealth.